Bureaucratic Transformation and Public Service Innovation in the Dynamics of Government Administrative Capacity in Dili City, Timor Leste - Roberto Jeronimo Cristovão; Emiliana Sri Pudjiarti (International Journal of Sociology and Law, 2026)
This study aims to analyze bureaucratic transformation and public service innovation in the dynamics of the administrative capacity of the Dili City government, specifically at the Cristo Rei District Office, in realizing responsive, accountable, and quality public services. The research approach employed a mixed methods approach, collecting quantitative data through questionnaires from 12 respondents and qualitative data through in-depth interviews with four key informants: Fernando Araujo (District Head), Marciana de Jesus Soares (Head of Administration and Finance), Jose Sarmento (Head of Program Planning), and Ernesto Mendonça (Head of Public Relations). Statistical analysis showed that institutional capacity had a very strong influence on public accountability (r = 0.806; p = 0.002), while bureaucratic responsiveness had a very strong influence on the quality of public services (r = 0.727; p = 0.007). The interviews revealed concrete practices of bureaucratic transformation, such as effective internal coordination, orderly administrative procedures, one-stop service, and responsiveness to citizen needs. This study indicates that institutional capacity and bureaucratic responsiveness are the dominant factors in improving service quality, while formal accountability needs to be made more open and participatory. The findings support the Theory of Administrative Capacity and the New Public Service, and offer recommendations to strengthen participatory mechanisms and make performance evaluation more transparent.